Profiling Serum Bile Acid Glucuronides in Humans: Gender Divergences, Genetic Determinants, and Response to Fenofibrate. Issue 4 (12th June 2013) - Trottier, J; Perreault, M; Rudkowska, I; Levy, C; Dallaire‐Theroux, A; Verreault, M; Caron, P; Staels, B; Vohl, M‐C; Straka, R J; Barbier, O
<x xml:space="preserve">Abstract</x> Glucuronidation, catalyzed by uridine 5′‐diphospho‐glucuronosyltransferase (UGT) enzymes, detoxifies cholestatic bile acids (BAs). We aimed to (i) characterize the circulating BA‐glucuronide (BA‐G) pool composition in humans, (ii) determine how sex and UGT polymorphisms influence this composition, and (iii) analyze the effects of the lipid‐lowering drug fenofibrate on the circulating BA‐G profile in 300 volunteers and 5 cholestatic patients. Eleven BA‐Gs were determined in pre‐ and postfenofibrate samples. Men exhibited higher BA‐G concentrations, and various genotype/BA‐G associations were discovered in relevant UGT genes. The chenodeoxycholic acid‐3G (CDCA‐3G) concentration was associated with the UGT2B7 802C>T polymorphism. Glucuronidation assays confirmed the predominant role of UGT2B7 and UGT1A4 in CDCA‐3G formation. Fenofibrate exposure increased the serum levels of five BA‐G species, including CDCA‐3G, and upregulated expression of UGT1A4, but not UGT2B7, in hepatic cells. This study demonstrated that fenofibrate stimulates BA glucuronidation in humans and thus reduces BA toxicity in the liver. Clinical Pharmacology & Therapeutics (2013); 94 4, 533–543. doi:10.1038/clpt.2013.122